2017
DOI: 10.1007/s10661-017-6238-2
|View full text |Cite
|
Sign up to set email alerts
|

Annual and intradiurnal variation of dominant airborne pollen and the effects of meteorological factors in Çeşme (Izmir, Turkey)

Abstract: In this present study, airborne pollen in Çeşme was investigated between February 17, 2012 and February 17, 2014 using the volumetric method. Çeşme, one of Turkey's most important tourism centers, which attracts numerous local and foreign tourists each year, is a district of Izmir, a province in the western part of Turkey. During the 2-year study, 12,905 pollen grains belonging to 64 taxa (33 arboreal, 31 non-arboreal plants) were detected. However, the 2-year data results revealed that the taxa with the polle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
1
7
0
1
Order By: Relevance
“…atmospheric pollen concentration of many cities in Turkey (İnce, 1994;İnceoğlu et al, 1994;Pehlivan and Butev, 1994;Öztürk, 2002, 2003;Ayvaz et al, 2008;Tosunoğlu et al, 2015aTosunoğlu et al, , 2015bBıçakçı et al, 2017;Uğuz et al, 2017Uğuz et al, , 2018 and also in other countries (Nilsson et al, 1977;Goldberg et al, 1988;Subiza et al, 1995;Abreu et al, 2003;Boral et al, 2004;Docampo et al, 2007).…”
mentioning
confidence: 99%
“…atmospheric pollen concentration of many cities in Turkey (İnce, 1994;İnceoğlu et al, 1994;Pehlivan and Butev, 1994;Öztürk, 2002, 2003;Ayvaz et al, 2008;Tosunoğlu et al, 2015aTosunoğlu et al, , 2015bBıçakçı et al, 2017;Uğuz et al, 2017Uğuz et al, , 2018 and also in other countries (Nilsson et al, 1977;Goldberg et al, 1988;Subiza et al, 1995;Abreu et al, 2003;Boral et al, 2004;Docampo et al, 2007).…”
mentioning
confidence: 99%
“…On the other hand, the main pollen seasons of these taxa extended to summer months and early fall; however, the recorded pollen concentrations were not very high in these months although temperatures were high. Similar studies also recorded a negative correlation between the pollen concentrations of these taxa and the average temperature (Tosunoğlu and Bicakci, 2015;Tosunoglu et al, 2018;Uguz et al, 2017 may have prevented flowering and thus caused a decrease in pollen counts (Çeter et al, 2012). Seasonal precipitation was another factor affecting the amount of airborne pollen in the atmosphere during spring, causing quantitative differences between the 2 years.…”
Section: Resultsmentioning
confidence: 78%
“…Today, the most common method for sampling pollen grains and sporesis the volumetric method; the Hirst-type trap is used worldwide for spore and pollen monitoring (Buters et al, 2018). In recent years, there has been a considerable increase in the number of studies using the volumetric method in Turkey (İnceoğlu et al, 1994;Guvensen and Ozturk, 2003;Potoğlu Erkara et al, 2007;Bicakci et al, 2017;Uguz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The latter study, the oldest one found, describes 35 pollens, each of which dispersed according to their own timing; the common element being that this dispersion only occurred during the day. Generally, the publications found high pollen concentrations at midday and low concentrations at night, based on sampling in Turkey, Portugal, and Germany [40-42]. A number of studies presented the measurement of a particular pollen, but the results are not consistent.…”
Section: Evaluation Of the Scientific Relevance Of The Guidelinesmentioning
confidence: 99%